Variation in Photovoltaic Energy Rating and Underlying Drivers Across Modules and Climates - Kevin S. Anderson; Joshua S. Stein; Marios Theristis (IEEE Access)
The performance of photovoltaic (PV) modules is determined by the interplay between their inherent characteristics and the prevailing weather conditions. Although the impacts of different characteristics (e.g., low-light behavior, spectral mismatch, temperature coefficient, etc) are known, they have not been quantified over large geographic regions. This study uses the Climate Specific Energy Rating (CSER) and specific yield metrics as criteria to determine how different PV modules perform across climates in the contiguous United States (CONUS) and identifies the underlying drivers behind the observed variations. The annual CSER and specific yield of various PV technologies vary by more than 10% and 30%, respectively, across the CONUS. As expected, temperature has the most significant impact on CSER, affecting CSER by up to 13.1%, while spectral effects account for up to 4.9% variation in the case of cadmium telluride modules. Additionally, minor differences in parameter estimation procedures are shown to result in CSER differences of up to 1.5% in some climates. Furthermore, the IEC 61853-4 reference climatic datasets are found to overestimate CSER by 2–4% relative to climatic data for locations of actual PV systems in the United States. A new set of reference locations that accurately represents CSER across CONUS is proposed as an alternative to the IEC 61853-4 reference datasets.